Design and Evaluation of a New Type of Knee Orthosis to Align the Mediolateral Angle of the Knee Joint with Osteoarthritis - Amir Esrafilian; Mohammad Taghi Karimi; Arezoo Eshraghi (Advances in Orthopedics)
Background. Osteoarthritis (OA) is a disease which influences the performance of the knee joint. Moreover, the force and moments applied on the joint increase in contrast to normal subjects. Various types of knee orthoses have been designed to solve the mentioned problems. However, there are other problems in terms of distal migration during walking and the alignment of the orthosis which cannot be changed following the use of brace. Therefore, the main aim of the research was to design an orthosis to solve the aforementioned problems. Method. A new type of knee orthosis was designed with a modular structure. Two patients with knee OA participated in this research project. The force applied on the foot, moment transmitted through the knee joint, and spatiotemporal gait parameters were measured by use of a motion analysis system. Results. The results of the research showed that the adduction moment applied on the knee joint decreased while subjects walked with the new knee orthosis (P-value < 0.05). Conclusion. The new design of the knee brace can be used as an effective treatment to decrease the loads applied on the knee joint and to improve the alignment whilst walking.